Irradiation of fresh volvariella volvacea mushrooms hysiological, biochemical and sensory quality aspects - Mercado, Lydia Nayga; Alabastro, Estrella F. (1980., 1980)
Freshly harvested Volvariella volvacea mushrooms in the first flush stage (10-14 days old) packed in LDPE bags perforated to about 0.3% aeration were irradiated with 50 and 100 kr of gamma radiation from a Gamma Cell 220 with a Co-60 irradiation unit delivering a dose rate of 257-260 kr/hr. The effects of ionizing radiation on certain physiological processes, biochemical changes and sensory qualities of the mushrooms were investigated at specified periods of storage under controlled conditions of temperature (22-25%) and relative humidity (85-95%). ANOVA results show no significant differences in weights between treatments in all storage periods. Duncan's multiple range tests show significantly (p≤0.05) lower percentages of buttons without defects in the controls compared with the 50 and 100 kr treated mushrooms. Irradiation at 50 and 100 kr definitely delays and inhibits veil opening and significantly suppresses the respiration rate. As the respiration rate of irradiated mushrooms decreases with storage, the reducing sugars concentration increases. Gamma radiation produces a significant decrease in polyphenol oxidase activity with storage time in contrast to an increased activity in the controls. Irradiation at 50 or 100 kr significantly improves the color, texture/appearance and odor of fresh mushrooms. The findings of this study indicate that mushrooms irradiated at 50 or 100 kr can be stored for 4 days without refrigeration with 84% marketability.
Mimeographed.
Thesis (Ph.D. Food Science)--University of the Philippines, Quezon City.
Keywords: Mushrooms; Food, Effect of radiation on; Food, Irradiated